Effects Of Extraction Conditions And Altered Solvent Environment On The Functionality Of The Food Macromolecules Of Pigeonpea (Cajanus Cajan L.) And Cowpea (Vigna Unguiculata L.) - Mwasaru, Mwanjala Alfred (1996)

(untitled)
The extractability of the proteins from pigeonpea and cowpea seeds was influenced by extraction techniques and conditions; the micellization technique extracted 40.2 and 36.7% of the total seed protein, respectively. The isoelectric precipitation technique extracted 35.1 to 58.1% and 36.4 to 53.5% of the seed protein, respectively at extraction pH 8.5-12.5. The purity of the isolates was in the range of 78.1 to 92.9%, and for the isoelectric isolates, it was inversely correlated to extraction pH. The isolates were free of the antinutrients associated with the legume seeds, however, extraction technique had no effect on the subunit composition and electrical mobility. An inverse relationship was evident between the lightness colour value (L) of the isoelectric isolates and the pH of extraction for pigeonpea (R2=0.76) and cowpea (R2=O.77), and the micelle isolates were lighter in colour than the isoelectric isolates. All the isolates presented typical solubility profiles, however, significant quantitative differences were observed; the micelle isolates exhibited superior solubility characteristics to the isoelectric isolates and for the latter an inverse relationship between solubility and extraction pH was apparent.